Analysis of Expected Stock Returns in 2020 - 2022 Using Arbitrage Pricing Theory (Study on Stocks Incorporated with The IDX-30 Index on The Indonesia Stock Exchange) - Harold Kevin Alfredo (Green Publisher Indonesia, 2023)
This study aims to determine which IDX-30 member stock issuers have the highest expected return values in 2020, 2021, and 2022, and macroeconomics which have a high influence on the expected returns of IDX-30 member stock issuers in 2020, 2021, and 2022. The population in this study is all stock issuers who are registered as IDX-30 members in 2020, 2021, and 2022, and the stock data taken is the issuer's stock data from 2020, 2021, and 2022. Stock price data and prices The JCI index is taken from the Investing.com website, and data on stock issuers who are members of the IDX-30 2020 – 2022 are taken from the doctorsaham.com website. Bond data is obtained from the KSEI website. Inflation data and USD exchange rate data taken are monthly data from December 2019 – December 2022. Inflation data is taken from the BI.go.id website, and USD exchange data is taken from satudata.kemendag.go.id website. The sample in this study is all members of issuer shares who consistently join as IDX-30 members in 2020, 2021 and 2022. The number of IDX-30 samples in 2020 is 27 issuers of shares, in 2021 there are 26 issuers of shares, and in 2022 there are 26 stock issuers. Calculating expected stock returns using the Arbitrage Pricing Theory, and ranking expected stock returns is done in the Microsoft Excel application, and Linear Regression is used to test the hypothesis in the JASP application